Sistematización EAPEAT carnaval de negros y blancos Pasto Nariño 2019 (2019)
The work of systematization of the Artistic-Pedagogical Experience to the Current State of the Tradition, presents the participative experience lived by the teachers in formation of the Degree in Scenic Arts, carried out in Pasto Nariño, from January 1 to 6, 2019, in the framework of the Black and White Carnival, gathered through the testimonies of the Narvaez family, artisans of ample tradition in Pasto Nariño Colombia, who shared all their experience and process of creation of their work, this information was obtained by means of video, audio and photography. The steps of the artistic creation, result of the EAPEAT Narváez What's in the crop, and the processes of compilation of the material and realization of the audiovisual memory are also presented.